2017
DOI: 10.7150/ijms.17821
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sterol Regulatory Element-Binding Proteins in epicardial adipose tissue in patients with coronary artery disease and diabetes mellitus: preliminary study

Abstract: Objectives: Sterol regulatory element-binding proteins (SREBP) genes are crucial in lipid biosynthesis and cardiovascular homeostasis. Their expression in epicardial adipose tissue (EAT) and their influence in the development of coronary artery disease (CAD) and type-2 diabetes mellitus remain to be determined. The aim of our study was to evaluate the expression of SREBP genes in EAT in patients with CAD according to diabetes status and its association with clinical and biochemical data.Methods: SREBP-1 and SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…EAT represents a visceral brown-like adipose tissue located between the myocardium and the inner layer of visceral pericardium with a close anatomical proximity to the myocardium 4 . A functional EAT has been proposed to play a protector role over the myocardium but in pathological situations may be implicated in the development and/or progression of heart disease 3 - 5 . Several studies have shown that EAT is associated with the pathogenesis of HF, but focusing on EAT volume determined by echocardiography, magnetic resonance or computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…EAT represents a visceral brown-like adipose tissue located between the myocardium and the inner layer of visceral pericardium with a close anatomical proximity to the myocardium 4 . A functional EAT has been proposed to play a protector role over the myocardium but in pathological situations may be implicated in the development and/or progression of heart disease 3 - 5 . Several studies have shown that EAT is associated with the pathogenesis of HF, but focusing on EAT volume determined by echocardiography, magnetic resonance or computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of mirna-122 leads to a decrease in total cholesterol and triglyceride in plasma (49). at present, lncrnas have emerged as critical factors in the promotion of hepatic gluconeogenesis and cholesterol biosynthesis via the SreBP pathway (46). However, their functions in cad remain unknown, which highlights the importance of the results of the present study.…”
Section: Discussionmentioning
confidence: 64%
“…Increasing studies have focused on the correlation between SREBP and cad. SreBP is upregulated in patients with cad and is a cardiovascular risk factor for the severity of cad and poor lipid control (46). Another study identified that the recessive allele (TT vs. CT+CC) of SREBP1 rs9902941 is highly expressed in patients with cad compared with the normal control (47).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high levels of myocardial SREBP1 have been reported in patients with pressure overloaded heart and metabolic syndrome [50] and might be causally related to selective insulin resistance and inhibition of uncoupling protein 3 (UCP3) expression in the mouse heart [51]. Besides, the high expression of both SREBP1 and SREBP2 mRNA in epicardial adipose tissue has been identified as a cardiovascular risk factor in patients with type-2 diabetes [52]. Myocardial SREBP1c is also involved in the regulation of cardiac parasympathetic response [11].…”
Section: Discussionmentioning
confidence: 99%